Patient journey in cystinosis: focus on non-adherence and disease management - Gema Ariceta; Simón Lalanza; Catalina Peña; Marta Martínez Montero; Carlos Bezos Daleske; Laura Acuña Álvarez; Elisa Giner (Drugs in Context)
Background: Few studies have assessed patient-reported experience measures in nephropathic cystinosis. This study uses patient reports focused on the impact of cystinosis, cysteamine treatment-associated problems, and therapeutic adherence and suggests potential actions for improvement.